Sub-Acute Toxicity and Allergy Studies of Bidara Leaf (Ziziphus Mauritiana) Extract as A Wound Healing Material - Ma'ruf, Mochammad Taha; Dewi, Putu Sulistiawati; Poernomo, Hendri (Odonto : Dental Journal, 2023)
Background: In dentistry, the wound healing process is often encountered in tooth extractions, incisions, oral and facial surgery, gingival flaps and biopsies. Post-tooth extraction wound is a medium that allows pathogenic microbes to breed and infect the wound. Wound management must be carried out as soon as possible to restore mucosal integrity so as to prevent bacterial infections penetrates the body. Bidara (Ziziphus mauritiana) is one of the plants used as traditional medicine by the community. Research on this plant as a medicinal raw material is increasing, so further research needs to be carried out to prove the safety of this medicinal plant. This study aims to determine the effects of sub-acute toxicity and allergic reactions caused after administering bidara leaf extract on the liver histopathology of mice. Methods: In vivo laboratory experimental study using a post-test only control group design with 24 mice (Mus musculus). The research sample consisted of 4 groups, namely the control group given 0.3% Na-CMC, the treatment group given bidara leaf extract at a dose of 500 mg/kg BW, 600 mg/kg BW, and 700 mg/kg BW. The treatment extract was given orally for 28 days. Results: The results of the study showed that the dose of bidara leaf extract had an effect on the liver histopathology of mice, namely at doses of 600 mg/kg BW and 700 mg/kg BW it had a toxic effect that was visible from changes in liver cell structure. Allergy tests showed that bidara leaf extract did not cause allergic reactions in mice. Conclusion: It can be concluded that bidara leaf extract (Ziziphus mauritiana) does not cause allergies and at certain doses does not have toxicity in the liver of animals study.